Clinical characteristics, prescription patterns, and persistence associated with sacubitril/valsartan adoption: A STROBE-compliant study. Issue 30 (30th July 2021) - Chen, Wenwen; Liu, Yanyan; Tang, Longlong; Li, Zhenshan; Liu, Yanlin; Dang, Heqin
Abstract : Abstract: Sacubitril/valsartan (sac/val) was launched in China in 2018; however, the adoption of sac/val in real-world clinical practice has yet to be described. This study aimed to analyze real-world treatment patterns of sac/val using data from 3 tertiary hospitals in China. A non-interventional, retrospective cohort study of patients with Heart failure (HF) prescribed sac/val from 3 tertiary hospitals in China between January 1, 2018 and June 30, 2020 was conducted. The analysis included sac/val dose titration patterns and persistence during 6 months post-index. A total of 267 patients were included, with a mean age of 63.9 ± 13.1 years. At index, 27% of patients were prescribed sac/val 12/13 mg b.i.d., 63.7% were prescribed 24/26 mg b.i.d., 4.5% were prescribed the target dose of 49/51 mg b.i.d., and 4.8% were not prescribed according to the recommended dose. During the 6 months post-index, 8.3% of patients had only 1 dose titration record. Good therapeutic persistence was observed across sac/val doses, and only 15.7% of patients discontinued sac/val during the 6 months post-index. In China, the majority of patients prescribed sac/val are not initiated on the recommended dose nor up-titrated according to drug instruction. Notably, good persistence with sac/val is observed in the real-world cohort study.